PERLINDUNGAN HAK PEKERJA MIGRAN DALAM PIALA DUNIA FIFA DI QATAR 2022 - Hadyan Aptadhia Falah; Aji Wibowo (Faculty of Law, Universitas Trisakti, 2023)
Many issues have arisen during the construction of the stadium for the FIFA World Cup in Qatar in 2022. The study's characterization of the issue is the pay and death of migrant workers. The research approach uses normative legal analysis of qualitative data. According to research and discussion, migrant worker deaths frequently occur without clear investigation into the causes. Without a clear investigation into the causes of migrant worker deaths, the families of migrant workers who are left behind cannot get adequate compensation. the remuneration of migrant workers is also a problem that has not been resolved, even though Qatar has tried many solutions to overcome it, in practice, the right to wages is still often violated. The conclusion is that Qatar has violated the provisions of the Right to Life and the Right to Wages of migrant workers set out in Article 2 and Article 23 point (2) of the UDHR. Qatar is also negligent in carrying out its obligations as a state, by not protecting the rights of migrant workers, not investigating the deaths of migrant workers, and being unable to provide solutions to the deaths and wages of migrant workers.